2021
DOI: 10.30849/ripijp.v55i1.1444
|View full text |Cite
|
Sign up to set email alerts
|

Before and After the Pandemic: Alcohol Consumption and Related Problems in Argentina

Abstract: The impact of the COVID-19 pandemic and isolation measures on alcohol consumption remains unknown among Latin-American countries. This paper characterizes differences in alcohol consumption and related problems before and after the pandemic among Argentinians from different genders, age groups, income levels, and behaviors regarding the acquisition of alcoholic beverages. Through an online survey 1446 participants were assessed regarding four alcohol consumption dimensions (frequency, quantity, heavy episodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In addition, alcohol-related negative events among Argentine university students decreased significatively, probably due to the reduction in social meetings and the closure of drinking places [ 11 ]. Another study conducted in Argentina among the general population found an overall small reduction in usual alcohol intake, and a more profound reductions in binge drinking [ 12 ]. The greatest reductions in alcohol consumption were reported among the 14 to 24 year old age group.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, alcohol-related negative events among Argentine university students decreased significatively, probably due to the reduction in social meetings and the closure of drinking places [ 11 ]. Another study conducted in Argentina among the general population found an overall small reduction in usual alcohol intake, and a more profound reductions in binge drinking [ 12 ]. The greatest reductions in alcohol consumption were reported among the 14 to 24 year old age group.…”
Section: Introductionmentioning
confidence: 99%